Truth without objectivity - Kolbel, Max (Routledge, 2002)
Truth without Objectivity provides a critique of the mainstream view of 'meaning'. Koelbel examines the standard solutions to the conflict implicit in this view, demonstrating their inadequacy and developing instead his own relativist theory of truth. The mainstream view of meaning assumes that understanding a sentence's meaning implies knowledge of the conditions required for it to be true. This view is challenged by taste judgements, which have meaning, but seem to be neither true nor false.